2015
DOI: 10.1007/s13277-015-4605-6
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of Hsa-miR-1 and long noncoding RNA MALAT1 promotes triple-negative breast cancer development

Abstract: Recent studies demonstrated that long noncoding RNAs (lncRNAs) have a critical role in the regulation of cancer progression and metastasis. However, little is known about the mechanism through which metastasis-associated lung adencarcinoma transcript 1 (MALAT1) exerts its oncogenic activity, and the interaction between MALAT1 and microRNA remains largely unknown. In the present study, we reported that MALAT1 was upregulated in triple-negative breast cancer (TNBC) tissues. Knockdown of MALAT1 inhibited prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 33 publications
4
90
1
3
Order By: Relevance
“…In the present study, our results indicated that MALAT1 expression was up-regulated in multiple breast cancer cell lines compared with normal breast cell line, as well as in ER-positive breast cancer tissues compared with adjacent normal breast cancer tissues. These data correlated with previous studies indicating that MALAT1 was overexpressed in primary breast cancer and promoted proliferation of breast cancer cells [2729]. We identified for the first time that MALAT1 expression was correlated with ER and its target genes in breast cancer, providing a new perspective in MALAT1 function.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, our results indicated that MALAT1 expression was up-regulated in multiple breast cancer cell lines compared with normal breast cell line, as well as in ER-positive breast cancer tissues compared with adjacent normal breast cancer tissues. These data correlated with previous studies indicating that MALAT1 was overexpressed in primary breast cancer and promoted proliferation of breast cancer cells [2729]. We identified for the first time that MALAT1 expression was correlated with ER and its target genes in breast cancer, providing a new perspective in MALAT1 function.…”
Section: Discussionsupporting
confidence: 90%
“…Several signaling pathways have been proposed to explain the oncogenesis of MALAT1 in breast cancer. Jin et al demonstrated a reciprocal negative control relationship between MALAT1 and miR-1; MALAT1 might exert its function through the miR-1/slug axis [27]. Bamodu et al identified MALAT1 as a mediator of KDM5B oncogenic potential in triple-negative breast cancer, and could be reversed by hsa-miR-448 [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several miRNAs negatively regulate MALAT1 by facilitating its degradation [58]. For example, a very recent study has reported mutual negative correlation between MALAT1 and miR-1 in TNBC model [41]. This study revealed that in BC cells MALAT1 facilitated the expression of Slug , a pro-EMT gene, by negatively regulating the interaction of miR-1 and slug mRNA.…”
Section: Discussionmentioning
confidence: 92%
“…A MALAT1 transcript longer than 8,000 bps is abundantly expressed in the nucleus and is also known as nuclear-enriched abundant transcript 2 (NEAT2) [56]. MALAT1 was reported to be specifically up-regulated in many cancers, such as ovarian cancer, gastric cancer, and breast cancer, in several studies [5759]. High MALAT1 expression levels in cancer promote cell proliferation, migration and invasion.…”
Section: Lncrnas In Hncmentioning
confidence: 99%